2022
DOI: 10.3762/bjoc.18.136
|View full text |Cite
|
Sign up to set email alerts
|

Ionic multiresonant thermally activated delayed fluorescence emitters for light emitting electrochemical cells

Abstract: We designed and synthesized two new ionic thermally activated delayed fluorescent (TADF) emitters that are charged analogues of a known multiresonant TADF (MR-TADF) compound, DiKTa. The emission of the charged derivatives is red-shifted compared to the parent compound. For instance, DiKTa-OBuIm emits in the green (λPL = 499 nm, 1 wt % in mCP) while DiKTa-DPA-OBuIm emits in the red (λPL = 577 nm, 1 wt % in mCP). In 1 wt % mCP films, both emitters showed good photoluminescence quantum yields of 71% and 61%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…[ 32 ] The color purity of these results was better than that of recently reported LECs with MR‐TADF emitters. [ 33,34 ] Therefore, we concluded that the realization of ultrapure blue EL emissions based on solution‐processable LECs could contribute greatly to the creation of a sustainable society in the future.…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 ] The color purity of these results was better than that of recently reported LECs with MR‐TADF emitters. [ 33,34 ] Therefore, we concluded that the realization of ultrapure blue EL emissions based on solution‐processable LECs could contribute greatly to the creation of a sustainable society in the future.…”
Section: Resultsmentioning
confidence: 99%
“…After confirming a TADF emission mechanism, we turned our attention on the influence of ionic additives employed in the active layer of the final device, vide infra , as it has been demonstrated that the presence of ionic additives can alter similarly the spin-vibronic coupling. [21,31,57] Thus, morphology and photophysical response of films embedding dendrimers and ion polyelectrolyte was also studied. Since the appropriate selection of the electrolyte is crucial to meet high performing LECs, we explored a wide variety of traditional ion-based electrolytes in LECs, namely PEO-based electrolytes, ionic liquids, inorganic salts, etc.…”
Section: Photophysical Properties In Thin Filmsmentioning
confidence: 99%
“…40 Karaman et al recently reported on the synthesis of two cationic MR-TADF compounds, which comprised a DiKTa 41 core endowed with a chemically grafted imidazolium cation that is chargecompensated by a mobile PF 6 − anion. 42 They introduced a neat thin lm of one, or a blend, of these two ionic compounds as the active material in an LEC device, which delivered electroluminescence. The drawbacks were that the peak luminance and the EQE were modest at 15 cd/m 2 and < 0.01%, respectively, and that the emission spectrum was broad with a FWHM of > 100 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The drawbacks were that the peak luminance and the EQE were modest at 15 cd/m 2 and < 0.01%, respectively, and that the emission spectrum was broad with a FWHM of > 100 nm. 42 Here, we report on the development of the rst MR-TADF LEC that delivers bright and narrowband emission at 500 cd/m 2 and a FWHM of 31 nm, respectively, at a high EQE of 3.8%. The peak wavelength of the blue-emitting MR-TADF LEC is 489 nm and the CIE coordinates are (0.11, 0.35).…”
Section: Introductionmentioning
confidence: 99%